Modelling of soil loss using USLE through Remote Sensing and Geographical Information System in micro-watershed of Kashmir valley, India - KUMAR, ROHITASHW; KUMAR, MUKESH; SHAH, AMIR ISHAQ; BHAT, SHAKEEL AHMAD; WANI, M. A.; RAM, D. (Journal of Soil and Water Conservation, 2020)
The present study was conducted to prediction of soil loss using the Universal Soil Loss Equation (USLE) with the computer capabilities of a Geographical Information System (GIS), using the software package ArcGIS at Khimber micro-watershed of Dal Catchment in Kashmir valley. The USLE estimate the soil loss based on the relationships of factors; rainfall (R), soil erodibility (K), topography (LS), vegetation (C); and erosion control and practice (P). The input data of the factors for each field was derived from available land information and field survey. A digital elevation model (DEM) of study area was created by digitizing contour and grid themes for (K) and (C) factors. The topographic factor incorporates, the length factor (L) and the slope factor (S) of each field, required to compute the LS factor, were derived from field boundary information and DEM. A distribution map indicated the soil loss estimation of each field. The result shows that the average soil loss wasobtained 14.4 t/ha per year. It has also found that combining the USLE with ArcGIS tools is useful for estimating soil loss on a local scale forslope maintaining.